The Application of Beads Media to Improve the Dynamic Addition of Mathematics Learning Outcomes of Students with Hearing Impairment - Nastiti, Diah; Winarsih, Murni; Mulyeni, Trisna (Department of Special Education, 2024)
The aim of the study was to improve the learning outcomes of dynamic addition math using bead media for students with hearing impairments in class VI SLB Negeri 5 Jakarta. The study used an action research method. Data collection uses quantitative data from test results, while qualitative data is collected by observation, interviews and documentation. The subjects in this study were 4 students with hearing impairments. The research was carried out in 2 cycles, in cycle I 75% of students were able to reach / exceed the passing grade and achieve learning objectives while in cycle II 100% of students were able to exceed the KKM value and achieve learning objectives. The results showed that bead media was able to improve students' learning outcomes because it had a role as a bridge of information from teachers to students when planting the concept of dynamic addition material.